Macrófagos regulatórios controlam a inflamação e promovem a recuperação em modelo experimental de doença inflamatória intestinal - Tamara Cristina Moreira Lopes (2020)
Inflammatory bowel disease is a group of digestive system diseases of complex pathogenesis, multifactorial and symptomatic treatment, and there is still no effective curative treatment. The imbalance of the local immune response seems to be the main trigger of the disease. In this context, macrophages play a fundamental role in pathology, and paradoxically, in the maintenance of intestinal homeostasis. Therefore, in this work, we evaluated the role of macrophages through their functional reprogramming for different activation profiles and used the regulatory profile in a therapy proposal to control the disease. The colitis model was reproduced by the administration of dextran sodium sulfate (DSS 3%) to the mice for 7 days. The animals submitted to colitis induction showed important clinical changes, measured through the Disease Activity Index (DAI), in addition to macroscopic and microscopic lesions. In assessing the role of macrophages in the pathogenesis of the disease, animals with colitis received treatment with two doses of macrophages reprogrammed in vitro, intraperitoneally. The results showed that groups treated with classically activated macrophages had even more severe disease. Histologically, it is possible to observe extensive areas of edema with intense transmural inflammatory infiltrate, presence of abscesses and fusion of the crypts, resulting in loss of colon architecture. On the other hand, animals treated with regulatory macrophages showed a significant improvement in all parameters analyzed, resulting in a lower DAI. It was observed macroscopically the colon with normal aspect and microscopically preserved areas of colon architecture, with few areas of lesion of the mucosa and submucosa. Fluorescence images showed the migration of macrophages to the inflamed colon after intraperitoneal injection of these cells. Thus, our results demonstrate that the polarization of macrophages to a regulatory profile was decisive in controlling experimental colitis in mice and that macrophages are a potential therapeutic target to be explored in the control of inflammatory bowel diseases.